ANALISIS PENGELOLAAN ASET TETAP PEMINDAHTANGANAN DAN PENGHAPUSAN BARANG MILIK NEGARA (BMN) - Yustiana, Hana; Arifuddin; Kartini (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
This study aims to examine how the process of transferring BMN through online auctions is carried out by close bidding and deletion of BMN using the SAKTI application system (central integrated) to replace SIMAK-BMN which is located at the research site of the Pompengan Jeneberang-South Sulawesi River Basin Research Center (BBWS). places of internship activities) which will be carried out in September 2022-December 2022 which will be continued with an extension of observations at the end of March 2023 on 3,385 Registration Serial Numbers (NUP) which include State Property (BMN) including fixed assets which are included in the category of equipment and machine. The results of the transfer in the form of online auction sales obtained a positive impact in the form of a deposit to the state treasury Non-Tax State Revenue (PNBP) which was included in the sale of the equipment and machinery category in the amount of IDR 22,300,000.00 also with an auction fee of 2% (2 percent) of IDR 446,000.00. The position of the Planned Need for State Property (BMN) in 2023 shows streamlining for maintenance spending in the data. The use of an application that makes it easier to detail research object data in the form of BMN which is included in the deletion process in the form of SIMAK-BMN but migrating to SAKTI as a new system that still needs to be adaptive in use and coordinate between parties so that it can run smoothly.